204k views
4 votes
CAN SOMEONE HELP ASAP!!!

CAN SOMEONE HELP ASAP!!!-example-1
User Maxbester
by
4.9k points

1 Answer

7 votes

Answer:

( x-2)^2 + ( y+1) ^2 = 25

Explanation:

The equation of a circle is

( x-h)^2 + ( y-k) ^2 = r^2 where ( h,k) is the center and r is the radius

The center is ( 2,-1) and the radius is the difference from the center to a point on the circle

(2,4) and (2,-1)

since x is the same the radius is (4- -1) = 5

( x-2)^2 + ( y--1) ^2 = 5^2

( x-2)^2 + ( y+1) ^2 = 25

User Wander
by
5.0k points